2003
DOI: 10.1007/s00441-002-0696-7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and neurochemical features of the extrinsic and intrinsic innervation of the striated muscle in the porcine esophagus: evidence for regional and species differences

Abstract: Studies of the intrinsic and extrinsic innervation patterns of esophageal motor endplates (MEPs) are mainly confined to small rodents. Therefore, an immunocytochemical, denervation and tracing study was conducted on the pig, an experimental model in which the distribution of the striated esophageal muscle portion more closely resembles the human situation. The purpose of this study was to analyze the origin and neurochemical content of the nerve fibers participating in the myoneural synapse. Fifteen 6-week-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 38 publications
1
19
0
1
Order By: Relevance
“…The distribution observed concurs with ultrastructural studies in the pig where ICC have been described at the level of the myenteric plexus and deep muscular plexus in the ileum (Jiménez et al 1999) and the deep muscular plexus in the duodenum (Henry et al 1998). In the only other study to use Kit-immunohistochemistry in the porcine gastrointestinal tract, Kit-immunoreactive ICC were observed in the striated muscle region of the cervical and thoracic oesophagus (Wu et al 2003). The cells in that study were spindle-shaped with bipolar tapering processes similar to the bipolar intramuscular ICC observed in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…The distribution observed concurs with ultrastructural studies in the pig where ICC have been described at the level of the myenteric plexus and deep muscular plexus in the ileum (Jiménez et al 1999) and the deep muscular plexus in the duodenum (Henry et al 1998). In the only other study to use Kit-immunohistochemistry in the porcine gastrointestinal tract, Kit-immunoreactive ICC were observed in the striated muscle region of the cervical and thoracic oesophagus (Wu et al 2003). The cells in that study were spindle-shaped with bipolar tapering processes similar to the bipolar intramuscular ICC observed in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Zhang and Diamant noted that rhythmic esophageal contractions were not common when the UES did not show them (Zhang and Diamant, 1994). This does not exclude ICC from playing a role in the origin of the rhythmicity since ICC occur in the human striated muscle of the esophagus (Faussone-Pellegrini and Cortesini, 1986) as well as in the mouse (Rumessen et al, 2001) and pig (Wu et al, 2003). Furthermore, when cell clusters were isolated from the rat esophagus, rhythmic contractions developed, dependent on the presence of ICC (Ludlow et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ICC in the striated muscle of the mouse appear to be uniquely associated with intrinsic inhibitory nerves, primarily nitrergic nerves (Rumessen et al, 2001; Wu et al, 2003). Paterson showed that balloon distention in the opossum esophagus generates myogenic contractions that increase in amplitude after TTX administration, indicating physiologically that the musculature is under tonic inhibitory control (Muinuddin and Paterson, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…There are also strain differences in rats in the extent to which nitrergic neurons are protected. 7,31 nNOS gene expression, nNOS synthesis and catalytic activity decreased in the myenteric plexus of aged rats. 16 There was an age-dependent reduction in AChrelease in the rat colon myenteric plexus between 4-to 8-month and 22-to 28-month-old rats.…”
Section: Nerve Sub-groupsmentioning
confidence: 94%